Ovarian cancer and BRCA mutation genetic testing: the Brazilian reality - Dalila Cunha de Oliveira; Luciana Lopes Mensor; Aniere Lima Banho; Guareide Carelli; Amanda Lins Acerbi; Andrea Paiva Gadelha Guimaraes; Angelica Nogueira-Rodrigues (Brazilian Journal of Oncology)
Introduction: Ovarian cancer (OC) is one of the leading causes of women’s cancer deaths worldwide. Recent clinical trials with PARP inhibitors showed promising therapeutic opportunities for OC patients. The assessment of BRCA mutation is well established as relevant in the prevention, early diagnostic, and family counseling for OC, and recently BRCA gene mutation was associated as a prognosis for PARP inhibitors treatment. In this scenario, the assessment of the patient’s mutation is proposed on Brazilian oncology guidelines and should be advised by health professionals that treat OC. Objectives: Inquire Brazilian oncologists about BRCA gene testing requesting time in the clinical practice for OC patients. Material and Methods: From May 2018 to June 2019, approximately 400 Brazilian oncologists received an online survey with questions related to the indication and challenges of BRCA gene testing. The survey was sent in 4 periods (waves); each wave received approximately 100 answers. Results: The compiled information showed that, on average, each oncologist treated 3 to 5 patients with ovarian cancer, they would recommend testing for three patients. Most respondents would indicate, BRCA testing during patients initial diagnostic period (w1=44%, w2=50%, w3=58%, and w4=64%). The sample of choice for testing would be blood/saliva assessing the germline mutational status (w1=35%, w2=43%, w3=46%, and w4=47%). The main reasons for oncologists to refrain from recommending BRCA testing were associated with cost and lack of reimbursement followed by lack of genetic counselors, among other factors. Conclusion: BRCA testing is restricted and not recommended for all ovarian cancer patients from the private health care sector. There is a lack of consensus on testing recommendations and discrepancies between coverage and national guidelines standardizing. There main difficulties associated with refraining testing were related to reimbursement and health plan coverage. Besides, the lack of genetic counseling was also pointed to as a bottleneck on oncologic patients’ multidisciplinary treatment.